ETIKA PRODUKSI DALAM ISLAM: TINJAUAN NARATIF TERHADAP UPAYA MEWUJUDKAN GREEN ECONOMY - Riko Haryanto; Abdul Azis; Nursaen Nursaen; Yayat Sujatna (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The global ecological crisis, triggered by the dominance of linear economic models and anthropocentric paradigms, demands a radical reorientation of the world's production systems. This article aims to analyze the discourse of Islamic production ethics as a philosophical and moral foundation for the realization of the Green Economy concept. Utilizing a qualitative approach with a narrative review method, this research explores the integration of Islamic theo-ecological pillars—Tawhid, Khalifah, Amanah, and Mizan—into contemporary green industrial policies. The findings indicate that Islamic production ethics offer a divine accountability framework that mandates the internalization of social and environmental costs, surpassing secular compliance standards that are often voluntary. The synthesis between the environmentally oriented Maqasid al-Shariah concept (Hifz al-Bi'ah) and circular economy strategies through the redefinition of